Breakdown voltage characteristics of combined air gaps under negative lightning impulse. (November 2022) - Wu, Shaocheng; Wang, Linong; Gao, Jiachen; Xie, Cheng; Song, Bin; Peng, Yong; Liu, Jianben; Liu, Yan
Abstract: Long air gaps are the main external insulation medium of overhead transmission lines. When there are floating conductors in the air gap, the gap's configuration changes, and the combined air gaps is formed. We built an experimental platform to obtain the breakdown characteristics of a 2 m rod–plane air gap with a rod floating conductor in different positions under negative lightning impulse. The results show that as the distance between the floating conductor and the high voltage conductor changes, the breakdown voltage (BV) and timing change. Moreover, the breakdown voltage increases with the length of sub-gap 1, showing a trend of first increasing, then decreasing, and then increasing, which is different from the trend under positive lightning impulse. The reason for this phenomenon is inferred from the analysis to be related to the polarity effect.